2005
DOI: 10.1086/426521
|View full text |Cite
|
Sign up to set email alerts
|

Bank Consolidation and the Dynamics of Consumer Loan Interest Rates

Abstract: The recent wave of bank mergers has raised concern over its effect on competition. This paper examines the influence of concentration and merger activity on consumer loan interest rates. It uses Bankrate, Inc. survey data on loan rates quoted weekly by large commercial banks in ten major U.S. cities during the period 1989 to 1997. The pricing behavior of banks is analyzed for two types of loans: new automobile loans and unsecured personal loans. Market concentration has a significant positive impact on the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 24 publications
(27 reference statements)
0
41
0
1
Order By: Relevance
“…Kahn et al (2000) found that mergers resulted in higher market rates on unsecured personal loans, but lower interest rates on automobile loans which are secured by liens. They stressed the importance of soft versus hard information.…”
Section: Depositors and Other Stakeholdersmentioning
confidence: 99%
“…Kahn et al (2000) found that mergers resulted in higher market rates on unsecured personal loans, but lower interest rates on automobile loans which are secured by liens. They stressed the importance of soft versus hard information.…”
Section: Depositors and Other Stakeholdersmentioning
confidence: 99%
“…But using weekly deposit rate changes as a proxy for deposit rate setting after a merger introduces a lot of noise. Therefore, as in Kahn et al (2005), we base our tests on rate changes computed over 4-week intervals. Our sample encompasses a total of 461 weeks, which allows us to construct a time series of 115 4-week intervals, which we refer to as "months" although they do not correspond to calendar months.…”
Section: Datamentioning
confidence: 99%
“…We base the empirical estimation on a unique dataset that is drawn from the full list of bank Kahn et al (2005), we base our tests on rate changes computed over four-week intervals.…”
Section: Datamentioning
confidence: 99%